Legal Protection of Billing Agency Workers - Radjawane, Jemy Marvel; Tjiptabudy, Jantje; Kuahaty, Sarah Selfina (TATOHI: Jurnal Ilmu Hukum, 2025)
Introduction: Humans as social creatures need help from other humans in living their daily lives. Because, there are things that humans cannot do without the help of other people. Apart from this, humans in their lives also have 3 (three) basic needs, namely: primary, secondary and tertiary needs. Facing these needs, both humans and companies always want to fulfill them all because they basically want to live a decent life and always have enough. To be able to meet these needs, what often happens is that people and companies do not buy goods in cash but rather in installments or on credit.Purposes of the Research:  Can a collection agency be said to be an employee? and what is the form of legal protection for collection agencies that take motor vehicles that are objects of credit guarantee.Methods of the Research: The research method used is a normative or literature legal research method.Results of the Research: The legal relationship between the debt collector and the debtor, namely the Billing Agency in doing its work acts as a lessor based on a power of attorney. The legal basis for the Billing Agency in carrying out its duties is carried out based on the granting of power of attorney from the lessor to the Billing Agency as stipulated in Article 1792 and Article 1795 of the Civil Code regarding special power of attorney.